Association Between Skin Tags and Acanthosis nigricans With GDM and Hypertensive Disorders of Pregnancy [39L]. (May 2017) - Park, YeonJung; Patwardhan, Sanjay; Chang, Eugene
Abstract : INTRODUCTION: Acanthosis nigricans (AN) and skin tags (ST) are associated with metabolic syndrome and insulin resistance in nonpregnant women. Studies have shown similar risk factors for metabolic syndrome and preeclampsia. The purpose of this study was to determine whether the presence of AN/ST are associated with increased risk of GDM and preeclampsia. METHODS: This was a prospective cohort study at MUSC. Patients ages 18-45 were examined at their prenatal visit for AN/ST and offered enrollment prior to their glucose tolerance test. Patients with pregestational diabetes, known fetal anomalies, and late transfers were excluded. A validated scale was used to assess AN. ST was defined as the presence of skin tags in the neck or axillae. Rates of GDM and hypertensive disorders of pregnancy were compared using chi square analysis with significance set at p < 0.05. RESULTS: 191 patients were enrolled but 24 dropped out. 81 of these patients had skin changes. 28.4% had AN and ST, 34.6% had just ST, and 37% had AN alone. No difference was found in GDM incidence between those with and without AN/ST (4.9% vs. 7%, p= 0.75). The presence of skin findings was significantly associated with an increased risk for hypertensive disorders of pregnancy (p < 0.001). CONCLUSION: The presence of AN/ST is not associated with an increased risk for GDM but associated with an increased risk for hypertensive disorders of pregnancy. Larger studies are warranted to explore this association. If valid, we may be able to identify women in whom low dose aspirin may be helpful.